Cuba – Asia y Oceanía: historical relations - Ruvislei Gonzalez Saez (Ибероамериканские тетради, 2021)
The countries of Asia and Oceania occupy a prominent place in Cuba’s foreign policy orientation, which is especially relevant today when the country is facing another strengthening of restrictions by the United States, as well as trying to overcome the crisis caused by the Covid-19 pandemic. The author analyzes the history and potential of Cuba’s cooperation with Asia, which is the most dynamic region in the world economy, in order to demonstrate the level of existing interaction and the prospects of emerging opportunities. The article provides an overview of the process of Cuba’s establishing diplomatic relations with the countries of Asia and Oceania, reflecting on both the incentives and the difficulties that accompanied this dynamic. The author looks at different areas of cooperation with the countries of the region, including health care (exchange of medical professionals, support by sharing medical brigades, shipments of diagnostic equipment and medications), agriculture and food security, academic exchange, etc. Particular attention is paid to trade, where economic ties with key partners are examined, taking into account the structure of trade. In conclusion, the research stresses the essential importance of developing already consolidated and trending relations between Cuba and the Asia-Pacific region, both with its “giants” and with the smaller states. This thesis is also supported by political preconditions, in particular by the fact that, from the political perspective, the countries of the region have expressed support and agreement with Cuba in many bilateral and multilateral aspects, especially those related to the condemnation of the U.S. economic and financial embargo against Cuba.